Self-trapping of polarons with off-diagonal coupling - Sun, Jin (2011)
A variational polaron wave function pioneered by Toyozawa is utilized to elucidate exciton-phonon correlations in a generalized Holstein Hamiltonian in the simultaneous presence of diagonal and off-diagonal exciton-phonon couplings. We show that a simple analysis of quantum entanglement between excitonic and phononic degrees of freedom allows one to effectively characterize both the small- and large-polaron regimes as well as the crossover in between.